2011
DOI: 10.1007/7854_2010_110
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila as a Model Organism for the Study of Neuropsychiatric Disorders

Abstract: The fruitfly Drosophila offers a model system in which powerful genetic tools can be applied to understanding the neurobiological bases of a range of complex behaviors. The Drosophila and human lineages diverged several hundred million years ago, and despite their obvious differences, flies and humans share many fundamental cellular and neurobiological processes. The similarities include fundamental mechanisms of neuronal signaling, a conserved underlying brain architecture and the main classes of neurotransmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 148 publications
1
17
0
Order By: Relevance
“…These simple animals share many complex traits with mammals, even at behavioral levels [36]. Furthermore, the major groups of ion channels are conserved, simplifying the dissection of core molecular machinery responsible for drug addiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These simple animals share many complex traits with mammals, even at behavioral levels [36]. Furthermore, the major groups of ion channels are conserved, simplifying the dissection of core molecular machinery responsible for drug addiction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, simple animals, such as C. elegans and Drosophila , share many complex traits with mammals, even at behavioral levels [36]. Therefore, the use of invertebrate model organisms may greatly simplify the dissection of core molecular machinery responsible for drug actions and addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila research has contributed to our understanding of nervous system development (Doe, 2008;Hartenstein et al, 2008), growth cone guidance and target recognition (Dickson, 2002), exocytosis and endocytosis at synapses (Bellen et al, 2010), synapse remodeling (Collins and Diantonio, 2007), and the neural circuitry underlying behaviors such as courtship (Villella and Hall, 2008), diurnal rhythms and sleep (Crocker and Sehgal, 2010), aggression (Kravitz and Huber, 2003), and learning and memory (McGuire et al, 2005). Moreover, it is now obvious that Drosophila is a good model organism to study genes that are involved in human disease, especially neurodegenerative mechanisms associated with Alzheimer disease, Parkinson disease, polyglutamine and other triplet repeat expansion diseases, amyotrophic lateral sclerosis, or neurological disorders such as epilepsy, depression and schizophrenia (Lu and Vogel, 2009;Lessing and Bonini, 2009;O'Kane, 2011). The toolkit is so extensive that it is becoming difficult to assess which tool is most appropriate for a particular application.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies have shown that 714 distinct human disease genes match 548 unique Drosophila sequences (6). Moreover, some of the genes that have been implicated in the pathogenesis of psychiatric diseases have counterparts in the Drosophila genome (7, 8). Taken together, these findings suggest that there may be an opportunity to study neuropsychiatric disorders in fruit flies.…”
Section: Introductionmentioning
confidence: 99%